Psychosocial Learning Environments of English Classes and Students’ Motivational Intensity in Learning English Language - Lemma W/Michael Gelete; Tamene Kitila Dhaba (ELT Worldwide: Journal of English Language Teaching, 2023)
The psychosocial learning environments of English classes could determine students’ motivation to learn English because students spend much amount of time in English classrooms which are the primary setting in which English learning occurs. This study investigated the extent to which English classroom psychosocial learning environments influence students’ motivational intensity in English learning. A correlational research design was used to attain this purpose. Simple random sampling was utilized to select 371 samples from the population. The data were gathered through “What Is Happening In this Class” and Motivational Intensity questionnaires, and were analyzed using inferential statistics. The results showed that each aspect of the psychosocial learning environment was related to students’ motivational intensity significantly. Further, the influence of the set of six psychosocial environment aspects on students’ effort and engagement in learning English was significant. Three of the six aspects, namely, task orientation, student involvement, and teacher support accounted for the influence on students’ motivational intensity significantly. This implies that students exert greater effort and engage in learning English when they are provided with a more task-oriented classroom environment, opportunities to be involved in the learning process, and adequate support from their English teachers. Therefore, the psychosocial environments of English classes need improvement to boost students’ motivation to learn English. In particular, the learning environment aspects of task orientation, student involvement, and teacher support play a vital role in motivating students to learn English.